Moving Beyond 'Better than Prison': How 'Alternatives to Imprisonment' are Experienced by Criminalized People and Staff - Morris, Victoria (Université d'Ottawa / University of Ottawa, 2026)
This doctoral dissertation explores the experiences of criminalized people and workers of initiatives that the Canadian federal government considers to be 'alternatives to incarceration'. Within the context of a penal paradox in which there are increased prison builds alongside stated efforts to address racism and colonialism within the penal system, it is important to examine the possibilities and pitfalls of initiatives said to be 'alternatives to incarceration'. Rooted in abolition geography and an abolitionist reform approach, this study explores how wards and workers of these initiatives experience care/support and coercion/control from staff and community-based 'correctional' institutions more broadly. The results indicate that although wards experience some benefits within these so-called alternatives to imprisonment, these initiatives are often experienced as extensions of the carceral structure, replicating many of the conditions and constraints of prison itself. Although these initiatives were often described as 'better than prison', the participants offered many suggestions for how to improve 'alternatives to imprisonment' and/or create new ones that address harms and/or meet basic needs of those who have been criminalized which would allow them to flourish, while decreasing or eliminating criminalization.
Keywords: Abolition; Alternatives to imprisonment; Reform; Care; Control